Coexistence of Axial Spondyloarthritis and Idiopathic Inflammatory Myopathy - Yongpeng Ge; Linrong He (Case Reports in Rheumatology)
Both axial spondyloarthritis (axSpA) and idiopathic inflammatory myopathy (IIM) are infrequent, and their coexistence is even rarer; there are a few reported cases in the literature. The aim of this study was to assess their association and clinical and laboratory features in our patients. The clinical data of patients with axSpA and IIM diagnosed in China-Japan Friendship Hospital from July 2015 to February 2019 were retrospectively analyzed. This study included 7 patients with axSpA who met the IIM criteria, including 3 males and 4 females. The age of onset was 16 to 39 years. Four patients were HLA-B27 positive, and three were negative. All patients were first diagnosed as axSpA, and then IIM was detected after 0.5–20 years (mean ± SD, 9.9 ± 5.0 years). After being diagnosed to have axSpA and IIM, those patients were given prednisone and immunosuppressant drugs, and their symptoms gradually improved. Our study provides further evidence of the coexistence of IIM with axSpA. In patients with axSpA who have skin rash, interstitial lung disease (ILD), myalgia, or muscle weakness, we should suspect that they may have IIM.